2022
DOI: 10.26418/jppk.v11i4.54416
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Strategies in Teaching Reading Comprehension

Abstract: The purpose of this research was to discover what strategies used by the English teacher and what strategies frequently used by the teacher in teaching reading comprehension Immanuel 2 Sungai Raya, Academic Year 2019/2020 by using questionnaire and depth interview. The subject of this research was an English teacher who has been teaching English since 2002 at the school. Besides being an English teacher, he is also a vice headmaster at the school. The type of this research was case study. The data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Additionally, teachers utilized strategies to capture students' attention, making academic activities more varied. It is expected that teachers will use various teaching strategies such as applying different teaching methods, media, and games to pique students' interest [28]. In this study, teachers enriched their teaching with various resources, depending on their confidence to experiment with blended approaches.…”
Section: Being Resourceful and Innovative In Teachingmentioning
confidence: 99%
“…Additionally, teachers utilized strategies to capture students' attention, making academic activities more varied. It is expected that teachers will use various teaching strategies such as applying different teaching methods, media, and games to pique students' interest [28]. In this study, teachers enriched their teaching with various resources, depending on their confidence to experiment with blended approaches.…”
Section: Being Resourceful and Innovative In Teachingmentioning
confidence: 99%
“…Previously, some researchers research the use of REAP strategy in teaching and learning contexts. In a research conducted by Martin et al (2015), the researcher found that the REAP strategy has a good impact on students' reading comprehension achievement of the text. Moreover, research was conducted by Oktavia Perwita Sari (2021)on her study found it was proved that the students score of reading using REAP strategy was better and it was effective to the students and really made sense for each student.…”
Section: Introductionmentioning
confidence: 99%
“…Reading is important as it is used to access alternative explanations and informations (Antoni, 2010;Nurhayati & Fitriana, 2018;Rusmanayanti & Hanafi, 2018). Reading is an important skill for the students in order to be able to understand written texts which involves active and complex processes (Gupta & Ahuja, 2014;Zand, 2015).…”
Section: Introductionmentioning
confidence: 99%